Keefektifan Konseling Behavioral Teknik Modeling dan Konseling Analisis Transaksional Teknik Role Playing untuk Meminimalkan Kecenderungan Perilaku Agresif Siswa Sekolah Menengah Atas - Gading, I Ketut; Nisa, Umrotun; Lestari, Luh Putu Sri (Jurnal Kajian Bimbingan dan Konseling, 2017)
This study aims to determine the effectiveness of behavioral counseling using modeling technique and counseling transactional analysis using role playing technique to minimize student’s tendency of aggressive behavior. This experimental research with pretest-posttest control group design is taking samples using purposive sampling technique. The sample were 18 tenth grade students from Senior High School Laboratorium Universitas Pendidikan Ganesha who have high aggressive behavior. 18 sample were randomly assigned to three group, that is: (1) experimental group of behavioral counseling using modeling technique; (2) counseling transactional analysis using role playing technique group; and (3) control group. Data on aggressive behavior tendency before and after treatment were collected using questionnaire of aggressive behavior, then analyzed by t test. The results show: (1) behavioral counseling using modeling technique were effective to minimize the tendency of aggressive behavior; (2) counseling transactional analysis using role playing technique were effective to minimize the aggressive behavior; and (3) counseling transactional analysis using role playing technique were more effectively minimizes the tendency of aggressive behavior rather than behavioral counseling using modeling technique.